Cloning of Escherichia coli and Pseudomonas aeruginosa phosphomannose isomerase genes and their expression in alginate-negative mutants of Pseudomonas aeruginosa. - Darzins, A (1985)
The phosphomannose isomerase (pmi) gene of Escherichia coli was cloned on a broad-host-range cosmid vector and expressed in Pseudomonas aeruginosa at a low level. Plasmid pAD3, which harbors the E. coli pmi gene, contains a 6.2-kilobase-pair HindIII fragment derived from the chromosome of E. coli. Subcloning produced plasmids carrying the 1.5-kilobase-pair HindIII-HpaI subfragment of pAD3 that restored alginic acid production in a nonmucoid, alginate-negative mutant of P. aeruginosa. This fragment also complemented mannose-negative, phosphomannose isomerase-negative mutants of E. coli and showed no homology by DNA-DNA hybridization to P. aeruginosa chromosomal DNA. By using a BamHI constructed cosmid clone bank of the stable alginate producing strain 8830, we have been able to isolate a recombinant plasmid of P. aeruginosa origin that also restores alginate production in the alginate-negative mutant. This new recombinant plasmid, designated pAD4, contained a 9.9-kilobase-pair EcoRI-BamHI fragment with the ability to restore alginate synthesis in the alginate-negative P. aeruginosa. This fragment showed no homology to E. coli chromosomal DNA or to plasmid pAD3. Both mucoid and nonmucoid strains of P. aeruginosa had no detectable levels of phosphomannose isomerase activity as measured by mannose 6-phosphate-to-fructose 6-phosphate conversion. However, P. aeruginosa strains harboring the cloned pmi gene of E. coli contained measurable levels of phosphomannose isomerase activity as evidenced by examining the conversion of mannose 6-phosphate to fructose 6-phosphate.